The Differences of Inpatients’ Satisfaction Level based on Socio-Demographic Characteristics - Ni Komang Ayu Adnya Dewi; Ni Putu Emy Darma Yanti; Kadek Saputra (Jurnal Ners, 2020)
Introduction: Assessing the quality of nursing care has become a global health issue. especially for caregivers and recipients of care in the inpatient department. Patient satisfaction is one of the  indicators to measure quality of nursing care. This study aimed to identify the differences of patient satisfaction level in inpatient ward based on socio-demographic characteristics at Siloam Hospitals Bali.Methods: This study was cross-sectional design with descriptive comparative and correlation methods. Patient satisfaction data were collected using the Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ) that was provided after the patient was discharged. Purposive sampling technique was used to determine 107 samples. The analytical tests used in this study were the Spearman correlation test, Mann-Whitney test and Kruskal-Wallis test.Results: The results of this study showed that there was a significant weak and negative correlation between the level of satisfaction and age of the patient (p = 0.017; r = -0.231; α <0.05). There were significant differences of patient satisfaction based on marital status (p = 0.036; α <0.05) and nationality status (p = 0.001; α <0.05), but there were no differences in patient satisfaction based on sex (p = 0.276; α <0.05) and education level (p = 0.434; α <0.05).Conclusion: This study concluded that social demographic characteristics of patients can influence the satisfaction, but only on age, marital and nationality status. This showed that inpatients provide good satisfaction evaluations of nursing care. The optimal nursing care needs to be maintained and improved, either routine evaluation or sustainable program development.